ORGANIZATION OF PRIMARY HEALTHCARE SERVICES FOR TUBERCULOSIS DIAGNOSIS AND TREATMENT - Mariana César dos Santos; Rayla Patrícia da Silva Andrade; Sonaly Melo de Macedo; Anny Suelen dos Santos Andrade; Tereza Cristina Scatena Villa; Érika Simone Galvão Pinto (Universidade Federal do Paraná, 2017)
The present study aimed to describe how Primary Care professionals, in the city of Natal, state of Rio Grande do Norte, perceive the organization of health care services for tuberculosis. Exploratory study, with a quantitative approach, carried out with 100 professionals of PHC, between November 2013 and January 2014. Data was collected with the use of a structured instrument. According to the results, 42% (n = 42) of the professionals affirmed that health unit managers play a key role in the planning for tuberculosis care; 43% (n = 43) reported that the agreed targets are periodically reviewed; 52% (n = 52) confirmed the existence of strategies to improve care services for tuberculosis; 56% (n = 56) mentioned the benefits and incentives offered to tuberculosis patients. It is concluded that the organizational capacity in primary care is related to governmental strategies aimed to ensure that health unit managers provide benefits and incentives to TB patients and that tuberculosis treatment is delivered at the primary care level.